2014
DOI: 10.1037/a0032722
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to improve follow-up for abnormal Papanicolaou tests: A randomized clinical trial.

Abstract: Objective To evaluate the effect of a theory-based, culturally-targeted intervention on adherence to follow-up among low-income and minority women who experience an abnormal Pap test. Methods 5,049 women were enrolled and underwent Pap testing. Of these, 378 had an abnormal result and 341 (90%) were randomized to 1 of 3 groups to receive their results: Intervention (I): culturally-targeted behavioral and normative beliefs + knowledge/skills + salience + environmental constraints/barriers counseling; Active C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
1
25
1
Order By: Relevance
“…18 Prior literature about culturally-targeted studies have suggested that targeting may be more effective with certain subgroups (based upon personal factors such as acculturation), 19 whereas other culturally-targeted studies have found no significant differences between groups. 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…18 Prior literature about culturally-targeted studies have suggested that targeting may be more effective with certain subgroups (based upon personal factors such as acculturation), 19 whereas other culturally-targeted studies have found no significant differences between groups. 21,22 …”
Section: Introductionmentioning
confidence: 99%
“…Initial adherence to abnormal Pap smear follow-up is inconsistently defined among published studies. Adherence has been defined as diagnostic colposcopy 3 months post-notification of an abnormal Pap smear test result [28,29], consistent with existing follow-up guidelines [30]. However, many studies do not differentiate timely versus delayed adherence [5,31] and define adherence broadly within a time frame ranging from 4 weeks to 18 months after receipt of an abnormal Pap smear test result [4].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Women from groups of racial/ethnic minorities and low education and income have limited access to healthcare and are less likely to seek care after an abnormal result. [4][5][6][7][8] In 1990, Freeman introduced the model of patient navigation as a way to support screening for, timely diagnosis of, and then treatment of cancer among vulnerable women. 9 The primary function of patient navigators is to reduce barriers to care by assisting participants in navigating the healthcare system.…”
mentioning
confidence: 99%